Four new species and a ribosomal phylogeny of Rhabdopleura (Hemichordata: Graptolithina) from New Zealand, with a review and key to all described extant taxa - Gordon, Dennis P.; Quek, Z. B. Randolph; Huang, Danwei (Zootaxa, 2024)
All eight extant species of Rhabdopleura described between 1869 and 2018 are provisionally accepted as valid based on a review of the literature and new data on two little-known species from the Azores. Additionally, four new species are described from the New Zealand region, increasing global diversity by 50%, and a dichotomous key to all 12 described species is provided based on morphological criteria. The distinction between colony morphologies based on erect-tube inception is regarded as particularly helpful in initial characterization of species. Erect ringed tubes are either produced directly from the surface of creeping-tubes or indirectly, i.e. a short adherent side branch from a creeping tube is interpolated between the creeping tube and an erect tube; such side branches are blind-ending. These two modes of erect-tube origination are here respectively termed direct and indirect. Species with indirect erect-tube budding are predominant in the North Atlantic whereas species with direct erect-tube budding dominate in New Zealand waters. The only indirect-erect species from New Zealand, Rhabdopleura chathamica n. sp., was discovered on deepwater coral from 1008‒1075 m, constituting the deepest record of the genus to date. Rhabdopleura emancipata n. sp., collected only in a detached state, constitutes a three-dimensional tangled growth that grew freely into the water column—a unique morphology hitherto unknown among extant species. Owing to this growth mode, it provided a substratum for epibionts from several phyla. Rhabdopleura francesca n. sp. and Rhabdopleura decipula n. sp. are morphologically very similar but are distinguishable by their distinct placements in a phylogeny based on 16S mitochondrial and 18S nuclear rRNA genes. Phylogenetic reconstructions based on rRNA and mitochondrial genome data contribute to an updated phylogeny of all Rhabdopleura species sequenced thus far, some of which require more molecular sequences and morphological analyses for taxonomic determination.